A Study on Performance Appraisal in Business School at Rewari - Dr. Saneh Yadav, Dr. Kapil dev , (International Journal of Scientific Research and Management (IJSRM), 2017)
Human resource management is the senses of getting things done through people ,is an essential part of every manager responsibility but many organization find it advantage to establish a specialist division to provide an expert service dedicated to ensuring that the human resource function is performed efficiently.”People are most valuable asset” is a cliché, which no member of any senior management team would disagree with. Yet, the reality for many business schools are that their people remain under valued under trained and underutilized. Performance appraisal is the process of assessing the performance and the progress of an employees or a group of employees on a given job and their potential for future development